Hubungan perilaku pencarian informasi dengan pemanfaatan media pembelajaran Edmodo - Dila Fauziah; Prijana Prijana; Asep Saeful Rohman (Universitas Padjadjaran, 2019)
Edmodo is one of the electronic learning or e-learning platforms that have advantages, one of which is a display similar to Facebook's social media. This study aimed to determine the relationship of the information-seeking behavior of students of ‘Sekolah Menengah Kejuruan Negeri’ (SMKN -Vocational High School) 1, Bandung, with the utilization of Edmodo learning media. This study examined the relationship between the drive for needs, creating change, and environmental activities with the utilization of Edmodo learning media. The method used a correlation study with a quantitative approach. The population in the study were students of class X SMKN 1 Bandung, amounting to 448 people. The sample of this study was 150 people. This research used the information-seeking behavior theory from Krikelas and the concept of Information Technology (IT) Utilization from Thompson. The correlation test analysis technique used Pearson Product Moment (PPM). The results showed that the drive for needs, creating change, and environmental activities, all had a significant relationship with Edmodo learning media. This study concludes that the relationship of information-seeking behavior with the utilization of Edmodo learning media has a low level of closeness. This condition is due to several factors, for Edmodo still functions as a complementary tool and diversity of other learning resources that support student information-seeking activities at SMKN1, Bandung.